2018
DOI: 10.1016/j.desal.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influence of module construction upon forward osmosis performance

Abstract: . (2018) 'Analysis of the in uence of module construction upon forward osmosis performance. ', Desalination., Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…an exact parallel with Figure 2 In a recent paper Field et al [11] presented a pair of equations relating flux, 'A', 'B' and the mass transfer coefficients and where the mass transfer coefficient, designated as , is the combined mass transfer coefficient for the support layer itself and the adjacent external mass transfer layer. The mass transfer coefficient for the support layer itself can be written as ⁄ where is the diffusivity of salt in water (it has a moderate dependency upon concentration [12]) and is the structural parameter, defined as the product of the support layer thickness and tortuosity over its porosity [13]:…”
Section: Reverse Osmosis Ulrafiltrationmentioning
confidence: 99%
“…an exact parallel with Figure 2 In a recent paper Field et al [11] presented a pair of equations relating flux, 'A', 'B' and the mass transfer coefficients and where the mass transfer coefficient, designated as , is the combined mass transfer coefficient for the support layer itself and the adjacent external mass transfer layer. The mass transfer coefficient for the support layer itself can be written as ⁄ where is the diffusivity of salt in water (it has a moderate dependency upon concentration [12]) and is the structural parameter, defined as the product of the support layer thickness and tortuosity over its porosity [13]:…”
Section: Reverse Osmosis Ulrafiltrationmentioning
confidence: 99%
“…The PRO process has a similar configuration to that of FO, except that the selective side of the membrane faces a higher concentration (draw) solution [ 39 , 40 , 41 ]. In PRO, the solution in the draw side is partially pressurised and kept below its osmotic pressure in order to create a net osmotic driving force for water to flow from the feed side to the draw side.…”
Section: Introductionmentioning
confidence: 99%
“…This fact is attributed to foulant-foulant-membrane interactions; accelerated flux decline (43%) was observed [51]. In contrast our results indicated that a flux of In practice, a flux determined found from a laboratory flat sheet unit should only be used as a guide because spiral wound modules themselves may well not achieve the same level of mass transfer [38] and we note that with a pilot-scale system, fouling control was achieved with a TFC spiral wound membrane as operated at a flux of 16.6 LMH [56]. Note: Flux recovery was by physical cleaning.…”
Section: Implication Of This Researchmentioning
confidence: 56%
“…Based on A, B and S determined before, the methodology of obtaining the best estimates of mass transfer coefficients was to change the value of kF and kD until a sum of square error (SSerr) between measured flux and estimated flux achieve a minimum value. The method has been used previously elsewhere [38]. The outcome is summarized in Table 1.…”
Section: External Concentration Polarizationmentioning
confidence: 99%